A Study of Work Culture in Scheduled Commercial Bank: Enhancing work culture in the banking sector (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper analyzes the study of work culture among the employees in the schedule commercial banks. While studying this topic special emphasis is made to highlight the work culture aspect. During this study around 60 respondents were selected at random from the public and private sector schedule commercial banks. Questionnaire method was used to collect data about the said topic. The result indicates that most of the employees are satisfied with their current job and work culture. Work culture does not really have significance between male and female employees. But the significant difference does lie in the level of job satisfaction on various factors like age, experience, productivity, morale, financial issues, banking policies, procedures and philosophies. This is indicated in the observation.Thus an attempt is made to study, analyze and understand the work culture in the given environment and in the organization. This paper will help organization especially the banking sector to adopt and adept suitable work culture to enhance the level of output from its employees to reach its desired goal.